2018
DOI: 10.3389/fmars.2018.00167
|View full text |Cite
|
Sign up to set email alerts
|

Aggregate Formation During the Viral Lysis of a Marine Diatom

Abstract: Recent studies have suggested that the viral lysis of microbes not only facilitates the conversion of particulate organic matter into dissolved organic matter, but also promotes the formation of organic aggregates, which enhance the export of organic carbon from the surface ocean to the deep sea. However, experimental data supporting this proposition are limited. Here, we tested the hypothesis that the viral infection of marine diatoms enhances aggregate formation. We used a model system consisting of Chaetoce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 43 publications
1
44
0
1
Order By: Relevance
“…A previous study revealed an increase in abundance of viruses infecting diatoms of Chaetoceros in both the water columns and the sediments during the bloom of their hosts in a coastal area ( Tomaru et al., 2011 ), suggesting sinking of cells caused by viruses. Furthermore, the diatom Chaetoceros tenuissimus infected with a DNA virus (CtenDNAV type II) has been shown to produce higher levels of large-sized particles (50–400 μm) compared with non-infected cultures ( Tomaru et al., 2011 ; Yamada et al., 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study revealed an increase in abundance of viruses infecting diatoms of Chaetoceros in both the water columns and the sediments during the bloom of their hosts in a coastal area ( Tomaru et al., 2011 ), suggesting sinking of cells caused by viruses. Furthermore, the diatom Chaetoceros tenuissimus infected with a DNA virus (CtenDNAV type II) has been shown to produce higher levels of large-sized particles (50–400 μm) compared with non-infected cultures ( Tomaru et al., 2011 ; Yamada et al., 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, a theoretical study proposed that the CEE increases if viral lysis augments the ratio of exported carbon relative to the primary production-limiting nutrients (nitrogen and phosphorous) ( Suttle, 2007 ). Laboratory experimental studies reported that cells infected with viruses form larger particles ( Peduzzi and Weinbauer, 1993 ; Yamada et al., 2018 ), can sink faster ( Lawrence and Suttle, 2004 ), and can lead to preferential grazing by heterotrophic protists ( Evans and Wilson, 2008 ) and/or to higher growth of grazers ( Goode et al., 2019 ). This process termed “viral shuttle” ( Sullivan et al., 2017 ) is supported by several field studies that reported association of viruses with sinking material.…”
Section: Introductionmentioning
confidence: 99%
“…The release of organic matter through the viral shunt has been estimated to be 150 billion tons of organic carbon per year [3]. A strong correlation between viral activity and carbon export by sinking particulate matter has recently been observed [9,10,11,12], indicating that viruses significantly contribute not only to the structuring of host communities, nutrient release, and ecosystem productivity, but also to the downward vertical transport of particulate carbon that comprises the biological carbon pump [2].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it is work with virus isolates in the laboratory that elucidated the role of virus-derived glycosphingolipids in terminating coccolithophore blooms and the rate-limiting biochemical steps in this process (Han et al, 2006;Vardi et al, 2012Vardi et al, , 2009, the competitive interactions between different coccolithoviruses (i. e., viruses infecting the E. huxleyi microalga) over the host for infection and the use of glycosphingolipid as virulence factors affecting viral success (Nissimov, Napier, Allen, & Kimmance, 2016;Nissimov et al, 2019), autophagy pathways in E. huxleyi during infection (Schatz et al, 2014), the virus strain-specific variations with regards to the induction of polysaccharide production in infected E. huxleyi cells (Nissimov et al, 2018), and the role of diatom-infecting viruses in aggregating material into sinking particles, important to the carbon biogeochemistry of the ocean (Yamada et al, 2018). Other notable examples where aquatic virus isolates were used to shed light on putative functions include the discovery of auxiliary metabolic genes (AMGs) in marine cyanophages (Breitbart, 2012), chlorovirus genes involved in carbohydrate metabolism (Van Etten et al, 2017), and genes involved in the production of fibers in Mimiviruses (Sobhy, La Scola, Pagnier, Raoult, & Colson, 2015).…”
Section: Classifying Cataloguing and Preserving Viruses Has An Unexpmentioning
confidence: 99%
“…Through this release (a process named "the viral shunt"), different metabolites and dissolved substances are remineralized and become readily available via the "microbial loop" to heterotrophic bacteria which utilise these as a food and energy source for growth (Azam, Fandino, Grossart, & Long, 1998;Pomeroy, Williams, le, Azam, & Hobbie, 2007;Wilhelm & Suttle, 1999). The second process is the "virus shuttle" which has a contrasting effect (Sullivan, Weitz, & Wilhelm, 2017;Yamada, Tomaru, Fukuda, & Nagata, 2018), in that the excreted metabolites and substances from the dying cells, which often include sticky polysaccharides and proteinaceous substances (Nissimov & Bidle, 2017;Thornton & Chen, 2017), clump cellular debris and other exuded compounds into larger particles of organic and inorganic material (Laber et al, 2018;Nissimov et al, 2018), which if heavy enough and negatively buoyant, sink through the water column, resulting in a net export of carbon from the surface ocean into the deep.…”
Section: Introductionmentioning
confidence: 99%